A5.02 Fluorescence optical imaging coupled with ultrasound radiography for detecting subtle hand inflammation in early rheumatoid arthritis. (24th February 2016) - Kisten, Y; Klint, E af; Györi, N; Rezaei, H; Levitsky, A; Karlsson, A; van Vollenhoven, RF
Abstract : Objectives: Fluorescence Optical Imaging (FOI) is an emerging modality that uses an intravenous fluorophore to display altered microcirculation (abnormal perfusion/capillary leakage) in synovial tissues in the hands. FOI can be analyzed visually (FOI-v) or by using automated Disease ACTivity (DACT). Using musculoskeletal ultrasound (MSUS) as a validated reference measure, we previously showed FOI to be highly sensitive and specific in detecting clinically manifest and silent synovitis in patients with various rheumatic diseases. Here, we analyze whether the same is true for early rheumatoid arthritis (eRA). Methods: Hands and wrists ineRA patients were assessed by clinical examination, MSUS and FOI-DACT. Active inflammation was defined as having synovial-hypertrophy/effusions and intra-articular Doppler signaling on MSUS, and as increased optical-intensities on FOI-v. Scores on DACT ≥ 1 was considered indicative of disease activity. Results: 39 eRA patients were studied [72% females, 56% previous/current smokers, 54% RF(+) and 69% ACCP(+)]. Of the 1326 joints in these patients, 303 were inflamed by clinical assessment, 380 by MSUS, and 400 by FOI-v. The percentages of patients and (mean ± SD) joints by clinical, MSUS and FOI-v were 69%(7.8 ± 8.1), 95%(9.7 ± 7.7), and 95%(10.3 ± 7.2), respectively. Using MSUS as reference, FOI-DACT was 95%(35/37) accurate in identifying patients with active disease, 24%(9/37) of whom had erosive RA. Good correlations noted between MSUS and FOI-v (rho = 0.803; p < 0.001), clinical assessment and FOI-v (rho = 0.732; p < 0.001), and MSUS and clinical (rho = 0.793; p < 0.001). The sensitivity, specificity, NPV and PPV of inflammation by FOI-v was 81%(308/380), 90%(854/946), 61%, and 96% respectively. Of the clinically negative but MSUS positive (145/1023) joints, 68%(98/145) were also FOI-v positive. Remarkably, one patient had 15 joints that were FOI-DACT positive and MSUS negative, but a month later, the same joints became MSUS positive. Although the wrists and MCPs were frequently inflamed, DIP joint inflammation was also seen in 34 and 14 joints in 12 patients by FOI-DACT and MSUS, respectively. Nine of these patients had osteoarthritis by conventional radiography. Conclusions: As reported for established rheumatic diseases, here we show high correlations and agreements between clinical examination, MSUS and FOI-v in detecting subtle inflammation in early RA as well. Moreover, DACT-FOI emerges as a useful automated quantitative scoring method for synovial inflammation in eRA. Reference: Kisten Y, Györi N, af Klint E, et al . 2015 Detection of clinically manifest and silent synovitis in the hands and wrists by fluorescence optical imaging. RMD Open . 1 : e000106. doi:10.1136/ rmdopen-2015-000106(http://rmdopen.bmj.com/content/1/1/e000106.full.pdf+html )